Raining in Quezon and Laguna: Revisiting Shared Folklore through the 1953 Historical Data Papers - Pawilen, Ryan Alvin M. (BANWAAN: The Philippine Journal of Folklore; Vol 3 No 02 (2023): Banwaan: The Philippine Journal of Folklore, 2025)
Rain and typhoons are common environmental experiences for local communities in the Philippines, a tropical country located in the typhoon belt. Building on the idea that shared natural hazards and environmental phenomena can lead to identical cultural expressions and practices, this paper undertook an exploratory cultural-historical study of similar folklore between the neighboring provinces of Laguna and Quezon. The study focused on beliefs, practices, and proverbs about rain, typhoons, and related concepts as recorded in the 1953 Historical Data Papers of the Philippines. The results were categorized into 'Causes and Human Intervention,' 'Rain Predictors,' and 'Rain in the Mental Landscape.' Aside from reflecting the interactions between humans, the environment, and spiritual factors, this type of folklore also reveals that the environment, particularly rain, exists both as an external natural entity and as an internal moral idea. Consequently, folklore about nature should therefore be considered a significant historical source, particularly in representing and understanding the everyday lives of the masses. Furthermore, this underscores the importance of the 1953 Historical Data Papers of the Philippines, which recorded and preserved local knowledge in the aftermath of World War II. Despite its limitations, the HDP can still yield valuable data for cultural history and folklore studies, as demonstrated in this paper. Keywords: rain, folklore, Historical Data Papers, Laguna, Quezon